Peningkatan Pendapatan Nelayan Di Desa Teluk Rhu Kabupaten Bengkalis Melalui Teknologi Diversifikasi Pangan Berbahan Dasar Hasil Perikanan - Feliatra, Feliatra; Batubara, Ummi Mardhiah; Mardalisa, Mardalisa; Kurnia, Pipin; Lukistyowati, Iesje; Ghazali, Tengku Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Teluk Rhu Village is a village that has potential in terms of fisheries and marine tourism. Some of the people in this village are fishermen, and the rest are fish farmers. The minimum knowledge and competence have fishermen in Teluk Rhu Village cause the welfare to be relatively low. To improve the fishermen's income needed knowledge improvement through food diversification technology based on fishery products. There are four methods used in this program, such as observation, material delivery, product manufacturing practices, and program evaluation. Twenty fishermen were participants and were involved very enthusiastically and actively in this program. There were two materials presented to increase fishermen's knowledge, including digital literacy and food innovation products. Lastly, all participants were trained to make several processed food products such as fish balls, nuggets, and fish sticks. The questionnaire data show that the community service program had several benefits for most participants. Thus, it's hoped that the new knowledge can make them more enthusiastic and motivated to begin a new businesses to increase family income.